Sistem Informasi Penjualan Perabot Rumah Tangga di Toko MD Sigambal Rantauprapat Berbasis Web - Pasaribu, Muhammad Arif (Universitas Labuhanbatu, 2022)
MD sigambal shop is one of the furniture stores that sell household furniture every day. various types of furniture produced are very varied and in accordance with consumer demand. in meeting consumer demands that are constantly changing, MD stores provide products with different amounts each day. this causes the MD sigambal store to be used as a place of research because the information system on the sale and purchase of furniture in that place has not been well managed so that there are often mistakes in the making of existing reports, such as uncertainty in producing the number of products (supplies). because it requires an accurate system for predicting the amount of furniture. This information system applies the waterfall model in its development and is built with the PHP programming language and uses MYSQL. program design that will be done with a reference program that is made using the UML (Unifed Modeling Language) method.